Dopant‐Free Small‐Molecule Hole‐Transporting Material for Inverted Perovskite Solar Cells with Efficiency Exceeding 21%. Issue 35 (11th July 2019) - Wang, Yang; Chen, Wei; Wang, Lei; Tu, Bao; Chen, Tian; Liu, Bin; Yang, Kun; Koh, Chang Woo; Zhang, Xianhe; Sun, Huiliang; Chen, Guocong; Feng, Xiyuan; et al.
Abstract: Hole‐transporting materials (HTMs) play a critical role in realizing efficient and stable perovskite solar cells (PVSCs). Considering their capability of enabling PVSCs with good device reproducibility and long‐term stability, high‐performance dopant‐free small‐molecule HTMs (SM‐HTMs) are greatly desired. However, such dopant‐free SM‐HTMs are highly elusive, limiting the current record efficiencies of inverted PVSCs to around 19%. Here, two novel donor–acceptor‐type SM‐HTMs (MPA‐BTI and MPA‐BTTI) are devised, which synergistically integrate several design principles for high‐performance HTMs, and exhibit comparable optoelectronic properties but distinct molecular configuration and film properties. Consequently, the dopant‐free MPA‐BTTI‐based inverted PVSCs achieve a remarkable efficiency of 21.17% with negligible hysteresis and superior thermal stability and long‐term stability under illumination, which breaks the long‐time standing bottleneck in the development of dopant‐free SM‐HTMs for highly efficient inverted PVSCs. Such a breakthrough is attributed to the well‐aligned energy levels, appropriate hole mobility, and most importantly, the excellent film morphology of the MPA‐BTTI. The results underscore the effectiveness of the design tactics, providing a new avenue for developing high‐performance dopant‐free SM‐HTMs in PVSCs. Abstract : Two novel donor–acceptor‐type hole‐transporting materials are developed and characterized. Due to the good energy level alignment, appropriate hole‐transporting ability, and most importantly, the excellent film morphology, the MPA‐BTTI‐based dopant‐free inverted perovskite solar cell exhibits a remarkable power conversion efficiency of 21.17% with negligible hysteresis and long‐time operational stability.